Hubungan Instructional Leadership dan Servant Leadership Kepala Sekolah Dasar dengan Mutu Pembelajaran di Era Society 5.0 - Royani, Nova Atika; Riswandi; Fatkhur Rohman; Nelly Astuti (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
The rapid development that occurs due to the industrial revolution 4.0 and society 5.0 causes many changes in the implementation of learning so that educators need to adapt and innovate in carrying out learning. The application of instructional leadership and servant leadership of school principals is needed in the professionalism of educators, especially in the era that continues to develop today so that it will determine the quality of school learning quality in the era of society 5.0. This study was conducted to determine the relationship between instructional leadership and servant leadership of elementary school principals with learning quality in the era of society 5.0. The population totalled 161 education personnel. The sampling was using proportionate stratified random sampling technique consisting of school principals and some educators in Gugus Matahari Natar District with a total of 63 respondents. The design used is a quantitative approach. The research data were collected through questionnaire and documentation techniques. The results showed that there is a significant relationship between instructional leadership and servant leadership of elementary school principals with the quality of learning in the era of society 5.0 with a correlation coefficient of 0.825 which is in the ‘Very Strong’ criteria. Keywords: leadership, learning quality, instructional, servant